Investigations on auditory spaciousness of large acoustic sources within a room - RUDNO-RUDZIŃSKI, K.; RENOWSKI, J. (Archives of Acoustics, 1990)
This paper presents results of a psychoacoustic experiment which consisted in length estimation of a quasi-Iinear horizontal sound source, performed by listeners. At preserved similarities of obtained dependences, considerable differences between responses of individual listeners were stated. Size evaluations dit not reflect the source’s length, but were in linear dependence with the maximal value of a normalized cross correlation function of signals reaching the listener’s left and right ear. An increase of sound level caused an increase of the source’s apparent length within the given series of estimations. Measurement results presented on the background of investigations on sound volume and sound spaciousness in concert halls indicate that volume and auditory spaciousness are different forms of the same impression quantity.